PENGARUH PEMBERIAN AIR REBUSAN DAUN SIRSAK (Annona muricata L) TERHADAP PENURUNAN KADAR ASAM URAT PADA PASIEN RAWAT JALAN DI PUSKESMAS PASAWAHAN - Nursoleha, Nela; Yani, Ahmad; Hermanto, Restu Amalia (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2019)
Background: Gout is a disease due to abnormalities purine metabolism (hyperuricemia). Increased uric acid production results from: excessive uric acid production, consumption of foods containing high purines, lack of drinking and physical activity. Soursop leaf have acetogenin and flavonoid compounds which help prevent the formation of uric acid. Method: This study was a pre-experimental study with a One group pre-post test design, with 31 subjects outpatients in Pasawahan Community Health Center, Purwakarta, uric acid levels were measured at the beginning of the study (pre-test), then patients were treated with soursop leaf boiled water treatment. Soursop leaf boiled water consists of 6 grams or 10 pieces of soursop leaf that have been washed clean and boiled with 600 ml of water that was cooked to boiling and the remaining 200 ml. administration was carried out for 7 consecutive days then uric acid levels were measured again on the 8th day (post-test). Analysis of the data used is the Paired T-test for the univariate test while the bivariate test uses the Spearman Rank and Pearson Product Moment. Results: The average value of uric acid levels before being given soursop leaf boiled water (pre-test) was 7, 16 ± 1, 25 mg/dl and uric acid levels after being given soursop leaf boiled water (post-test) was 7.15 ± 1,18 mg/dl. Conclusion: There was no effect of giving soursop leaf boiled water (Annona Muricata L) to decrease uric acid levels.